A fishbone-shaped CuBr nanocrystal and preparation method thereof
The preparation of fishbone CuBr nanocrystals through ultrasound assistance solved the problems of easy agglomeration, long preparation period and poor stability of CuBr nanocrystals, and achieved high specific surface area and low cost photocatalytic applications.
Patent Information
- Application Number
- CN202310664055.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-06-07
AI Technical Summary
CuBr nanocrystals are prone to agglomeration, resulting in low specific surface area, long preparation period and poor stability, making it difficult to effectively apply in the field of photocatalytics.
Ultrasonic assisted preparation of fish bone-shaped CuBr nanocrystals is used to adjust the reaction conditions and additives, and heat treatment is avoided, the preparation cycle is shortened, and the antioxidant properties of the products are improved.
The high specific surface area and good dispersion of fish bone-shaped CuBr nanocrystals are achieved, which reduces storage costs, simplifies the preparation process, and improves its application performance in the field of photocatalytics.
Smart Images

Figure CN116873968B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation, and in particular to a method for preparing fishbone-shaped CuBr nanocrystals. Background Art
[0002] In recent years, the contradiction between energy shortage and environmental pollution and the progress of people's production and life has become increasingly prominent. Semiconductor photocatalysts can directly decompose difficult-to-degrade organic matter (such as dyes) into carbon dioxide and water without any loss, and are known as "the most ideal environmental purification technology in the world today."
[0003] Since the introduction of photocatalytic technology, a variety of semiconductor photocatalysts have been developed. CuBr is a P semiconductor material with a zinc blende structure and a band gap of about 3eV. It has the advantages of low cost and non-toxicity. However, up to now, research on the photocatalytic degradation of dyes using nanostructured CuBr has not been reported. This is mainly due to the following problems in the preparation and storage of CuBr nanocrystals:
[0004] 1. The product is easy to agglomerate and the actual specific surface area is low
[0005] A larger specific surface area is an advantage of nanomaterials over traditional materials. In 2021, the applicant disclosed a method for preparing small-sized CuBr nanoparticles (CN202110259632.X). However, CuBr nanocrystals with a granular structure have high surface energy. In a thermal equilibrium state, adjacent nanoparticles are very easy to agglomerate in order to achieve a reduction in free energy. The agglomerated particles have a reduced specific surface area, resulting in a significant reduction in their application performance.
[0006] Compared with nanoparticles, nanocrystals with anisotropic structures can effectively inhibit agglomeration (due to the energy difference between adjacent interfaces). Therefore, the ability to prepare CuBr nanocrystals with anisotropic structures is of great significance for promoting the application of CuBr in the field of photocatalysis.
[0007] 2. Long preparation cycle and high actual cost
[0008] In 2022, the applicant disclosed a CuBr nanowire and its preparation method (CN202210017333.X). Studies have shown that Pd ions in the liquid phase can act as a structural directing agent, inhibiting the rapid aggregation of CuBr nanocrystal seeds and assisting the growth of CuBr nanocrystals along the
[110] crystal direction. However, the cost of Pd salts that act as structural directing agents is relatively high. The entire preparation process needs to be carried out at 90-99 degrees Celsius for 5-6 hours. Therefore, it is of great significance to be able to develop a low-cost method for preparing CuBr nanocrystals with anisotropic structures.
[0009] 3. Poor stability, the product is not easy to preserve
[0010] In 2008, Zhang Yongcai et al. from Yangzhou University used hydrothermal reduction technology to prepare nano-scale CuBr crystals ["Greenhydrothermal synthesis and optical properties of cuprous bromidenanocrystals." Materials Chemistry and Physics 108 (2008): 4-7]. The process selected copper sulfate pentahydrate as the precursor and glucose powder as the reducing agent. The entire preparation process was carried out at 100 degrees Celsius and the reaction took 12-14 hours. However, the CuBr crystals obtained by this method were easily oxidized and needed to be sealed under nitrogen protection.
[0011] Therefore, developing a CuBr crystal with oxidation resistance can effectively reduce the storage cost. It is of great significance to solve the storage cost of CuBr nanocrystals. Summary of the invention
[0012] The present invention aims to solve the problems mentioned in the background technology that CuBr nanocrystals are easy to agglomerate (low specific surface area), easy to oxidize (difficult to preserve), and have a long preparation cycle (high energy consumption). A method for preparing fishbone-shaped CuBr nanocrystals using ultrasound is provided, and the specific operation steps are as follows:
[0013] (1) using CuCl2 as a solute and deionized water as a solvent to prepare a CuCl2 solution with a concentration of 5.0-5.5 mg / mL, stirring and mixing the solution to obtain a mixed solution 1;
[0014] (2) adding a 0.5 mol / L hydrochloric acid solution to the mixed solution 1 in proportion, stirring and mixing uniformly to obtain a mixed solution 2;
[0015] (3) adding a certain amount of KBr powder to the mixed solution 2 in proportion and stirring evenly to obtain a mixed solution 3;
[0016] (4) adding an ascorbic acid solution having a concentration of 0.20-0.45 mol / L to the mixed solution 3 in proportion to obtain a mixed solution 4;
[0017] (5) using a 240 W ultrasonicator to sonicate the mixture for 10-20 minutes to obtain a white precipitate;
[0018] (6) Use a separatory funnel to separate the white precipitate obtained from the reaction from the reactants;
[0019] (7) The filtered white precipitate was washed once with 40 mL of deionized water and ethanol, and dried using a blower dryer.
[0020] (8) The obtained powder after drying is fishbone-shaped CuBr nanocrystals;
[0021] Correspondingly, the present invention also discloses a fishbone-shaped CuBr nanocrystal obtained by the preparation method of the fishbone-shaped CuBr nanocrystal.
[0022] The implementation of the present invention has the following beneficial effects:
[0023] 1. The present invention provides a method for preparing fishbone-shaped CuBr nanocrystals. No surfactant is added to the formula, and no toxic substances such as acetone and n-hexane are required for cleaning and purification in the later stage. The preparation process is environmentally friendly and the procedure is simple.
[0024] 2. The present invention utilizes ultrasonic mechanical energy to provide kinetic energy for the generation of CuBr, does not require heating treatment, has a short preparation cycle, can be achieved in 10-20 minutes, is carried out at room temperature, and is simple and easy to operate.
[0025] 3. The fishbone-shaped CuBr nanocrystals are not easy to agglomerate, and their good dispersion increases the specific surface area of the actual interface. The higher specific surface area contributes to its wide application in the field of photocatalysis.
[0026] 4. The obtained product has a certain degree of antioxidant properties, will not oxidize when placed in the air, does not require the addition of protective gas, and has low storage costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the X-ray diffraction pattern of the sample obtained in Example 1 of the present invention;
[0028] Figure 2 This is a field emission scanning electron microscope image of the fishbone-shaped CuBr nanocrystal obtained in Example 1;
[0029] Figure 3 This is a field emission scanning electron microscope image of the fishbone-shaped CuBr nanocrystal obtained in Example 2 of the present invention;
[0030] Figure 4 This is a field emission scanning electron microscope image of the fishbone-shaped CuBr nanocrystal obtained in Example 3 of the present invention;
[0031] Figure 5 This is a field emission scanning electron microscope image of the sample obtained in Comparative Example 1 of the present invention;
[0032] Figure 6 This is a field emission scanning electron microscope image of the sample obtained in Comparative Example 2 of the present invention;
[0033] Figure 7 This is a field emission scanning electron microscope image of the sample obtained in Comparative Example 3 of the present invention;
[0034] Figure 8This is the absorption spectrum of the photocatalytic degradation of methyl orange solution by the sample obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0036] Example 1: Preparation of fishbone-shaped CuBr nanocrystals 1
[0037] (1) Using CuCl2 as solute and deionized water as solvent, a 75 mL CuCl2 solution with a concentration of 5.1 mg / mL was prepared, and the mixture was stirred and mixed to obtain a mixed solution 1;
[0038] (2) preparing a 5 mL hydrochloric acid solution with a concentration of 0.5 mol / L, adding the solution to the mixed solution 1, and stirring to mix well to obtain a mixed solution 2;
[0039] (3) adding 2.0 g of KBr powder to the mixed solution 2 and stirring evenly to obtain a mixed solution 3;
[0040] (4) adding 25 mL of 0.45 mol / L ascorbic acid solution to the mixed solution 3 to obtain a mixed solution 4;
[0041] (5) using an ultrasonic device with a power of 240 W to sonicate the mixed solution 4 for 20 minutes to obtain a white precipitate;
[0042] (6) Use a separatory funnel to separate the white precipitate obtained from the reaction from the reactants;
[0043] (7) The filtered white precipitate was washed once with 40 mL of deionized water and ethanol, and dried in a 60 °C forced air dryer for 5 h;
[0044] (8) The white powder after drying is the fishbone-shaped CuBr nanocrystals.
[0045] In order to explore the composition of the obtained samples, we conducted an X-ray diffraction test on the product (exposed to air for 2 weeks), and the X-ray diffraction patterns were as follows: Figure 1 As shown, the product obtained corresponds completely to the characteristic peak of the No. 1-683 standard JCPDS card. Therefore, it can be known that the product obtained is CuBr. From the figure, no diffraction peaks of oxides (such as CuBr2 and CuO) are observed. Thus it is proved that the present invention proposes that the obtained CuBr nanocrystal has certain oxidation resistance and does not need to be stored under protective gas. This is because the ascorbic acid added in step 4) is excessive, which can also be adsorbed on the CuBr surface in addition to playing the role of reducing agent, isolating the contact with oxygen molecules in the air, and thus plays the role of antioxidant.
[0046] In order to obtain the morphology of the obtained sample, we conducted a field emission scanning electron microscope test on the sample obtained in Example 1. Figure 2 As shown, the obtained product is fishbone-shaped, with a single size of 5-8 μm. Due to the anisotropic morphology, the fishbone-shaped CuBr nanocrystals have good monodispersity.
[0047] The KBr powder added in step 5) of the present invention provides excess Br ions, a portion of which reacts with monovalent Cu ions to generate CuBr, and the other portion of bromine ions acts as a structure directing agent to assist the anisotropic growth of CuBr nanocrystals.
[0048] The generation dynamics of CuBr nanocrystals in the present invention is provided by the mechanical energy of the ultrasonic process. Since the energy of the mechanical wave under ultrasonic wave is discontinuous (changing with the ultrasonic frequency period), the CuBr is induced to grow into a fishbone shape.
[0049] Example 2: Preparation of fishbone-shaped CuBr nanocrystals 2
[0050] (1) Using CuCl2 as solute and deionized water as solvent, a 75 mL CuCl2 solution with a concentration of 5.0 mg / mL was prepared, and the mixture was stirred and mixed to obtain a mixed solution 1;
[0051] (2) preparing a 5 mL hydrochloric acid solution with a concentration of 0.5 mol / L, adding the solution to the mixed solution 1, and stirring to mix well to obtain a mixed solution 2;
[0052] (3) adding 2.0 g of KBr powder to the mixed solution 2 and stirring to mix them evenly to obtain a mixed solution 3;
[0053] (4) adding 25 mL of 0.45 mol / L ascorbic acid solution to the mixed solution 1 to obtain a mixed solution 4;
[0054] (5) using an ultrasonic device with a power of 240 W to sonicate the mixed solution 4 for 10 minutes to obtain a white precipitate;
[0055] (6) Use a separatory funnel to separate the white precipitate obtained from the reaction from the reactants;
[0056] (7) The filtered white precipitate was washed once with 40 mL of deionized water and ethanol, and dried in a 70 °C forced air dryer for 5 h;
[0057] (6) The white powder after drying is the target product.
[0058] Compared with Example 1, the ultrasonic time of Example 2 was shortened from 20 minutes to 10 minutes. In order to obtain the morphology of the obtained sample, we conducted a field emission scanning electron microscope test on the sample obtained in Example 2. Figure 3As shown, the obtained product is fishbone-shaped and the size of a single nanocrystal is 6 μm, which proves that the shortening of the reaction time does not change the morphology of CuBr.
[0059] Example 3: Preparation of fishbone-shaped CuBr nanocrystals
[0060] (1) Using CuCl2 as solute and deionized water as solvent, a 75 mL CuCl2 solution with a concentration of 5.0 mg / mL was prepared, and the mixture was stirred and mixed to obtain a mixed solution 1;
[0061] (2) preparing a 10 mL hydrochloric acid solution with a concentration of 0.5 mol / L, adding the solution to the mixed solution 1, and stirring the mixed solution 2;
[0062] (3) adding 4.0 g of KBr powder to the mixed solution 2 and stirring for 10 minutes to obtain a mixed solution 3;
[0063] (4) adding 50 mL of 0.22 mol / L ascorbic acid solution to the mixed solution 3 to obtain a mixed solution 4;
[0064] (5) using a 240 W ultrasonicator to sonicate the mixture for 20 minutes to obtain a white precipitate;
[0065] (6) Use a separatory funnel to separate the white precipitate obtained from the reaction from the reactants;
[0066] (7) The filtered white precipitate was washed once with 40 mL of deionized water and ethanol, and dried in a forced air dryer (70° C.) for 4 h;
[0067] (8) The white powder after drying is the target product.
[0068] In order to obtain the morphology of the obtained sample, we conducted a field emission scanning electron microscope test on the sample obtained in Example 3. Figure 4 As shown, the obtained product is fishbone-shaped. This proves that fishbone-shaped CuBr nanocrystals can be obtained under the synthesis concentration parameters within the scope of the claim.
[0069] Comparative Example 1: Effect of Ultrasonic Assisted Method on the Morphology of CuBr Nanocrystals
[0070] (1) Using CuCl2 as solute and deionized water as solvent, a 75 mL CuCl2 solution with a concentration of 5.0 mg / mL was prepared, and the mixture was stirred and mixed to obtain a mixed solution 1;
[0071] (2) preparing a 5 mL hydrochloric acid solution with a concentration of 0.5 mol / L, adding the solution to the mixed solution 1, and stirring the mixed solution 2;
[0072] (3) Add 2.0 g of KBr powder to the mixed solution 2 and stir for 10 minutes to obtain a mixed solution 3;
[0073] (4) adding 25 mL of 0.45 mol / L ascorbic acid solution to the mixed solution 3 to obtain a mixed solution 4;
[0074] (5) stirring the mixed solution 4 at room temperature for 20 minutes to obtain a white precipitate;
[0075] (6) Use a separatory funnel to separate the white precipitate obtained from the reaction from the reactants;
[0076] (7) The filtered white precipitate was washed once with 40 ml of deionized water and ethanol, and dried in a blower dryer (60° C.) for 5 hours.
[0077] (8) The white powder after drying is the target product.
[0078] Compared with Example 1, the room temperature ultrasound in step 5 of Comparative Example 1 is replaced by stirring. In order to obtain the morphology of the obtained sample, we performed field emission scanning electron microscopy test on the sample obtained in Example 1.
[0079] like Figure 5 As shown in the figure, without ultrasound, the obtained CuBr nanocrystals have poor monodispersity and fail to present a complete fishbone-shaped structure. The reason for this phenomenon is that the reaction kinetics provided by the stirring reaction is limited (low energy density), resulting in the inability of the CuBr nanocrystal core to grow into a complete fishbone-shaped morphology.
[0080] Therefore, it can be concluded that one of the key technologies for obtaining fishbone-shaped CuBr nanocrystals in the present invention is to use ultrasound as a reaction condition. High frequency / high energy density ultrasound is a necessary condition for the formation of complete fishbone-shaped CuBr.
[0081] Comparative Example 2: Effect of reaction rate on the morphology of CuBr nanocrystals 1
[0082] (1) Using CuCl2 as solute and deionized water as solvent, a 75 mL CuCl2 solution with a concentration of 5.1 mg / mL was prepared, and the mixture was stirred and mixed to obtain a mixed solution 1;
[0083] (2) After the mixed solution 1 is completely dissolved, 2.0 g of KBr powder is added thereto and stirred to uniformly mix, thereby obtaining a mixed solution 2;
[0084] (3) adding 25 mL of 0.45 mol / L ascorbic acid solution to the mixed solution 2 to obtain a mixed solution 3;
[0085] (4) using a 240 W ultrasonicator to sonicate the mixture for 20 minutes to obtain a white precipitate;
[0086] (5) Using a separatory funnel, the white precipitate obtained by the reaction was separated from the reactant, and the filtered white precipitate was washed once with deionized water and ethanol respectively, and dried in a 60°C forced air dryer for 5 hours to obtain the target product;
[0087] Compared with Example 1, no hydrochloric acid solution was added in the preparation process of Comparative Example 2 (the pH value of the reaction solution was higher). In order to obtain the morphology of the obtained sample, we conducted a field emission scanning electron microscope test on the sample obtained in Example 2, as shown in the attached figure. Figure 6 shown.
[0088] Compared with Example 1, the nanocrystals of Example 2 did not form complete fishbone-shaped CuBr nanocrystals. This is because the reaction rate of Example 2 was too fast (due to the high pH value), and the faster kinetics could not form a complete fishbone-shaped structure under microwave assistance.
[0089] Comparative Example 3: Effect of reaction rate on the morphology of CuBr nanocrystals 2
[0090] (1) Using CuCl2 as solute and deionized water as solvent, a 75 mL CuCl2 solution with a concentration of 5.0 mg / mL was prepared, and the mixture was stirred and mixed to obtain a mixed solution 1;
[0091] (2) preparing 10 mL of 0.5 mol / L hydrochloric acid solution, adding it to the mixed solution 1, and stirring to mix evenly to obtain a mixed solution 2;
[0092] (3) adding 4.0 g of KBr powder to the mixed solution 2 and stirring to make it uniformly mixed to obtain a mixed solution 3;
[0093] (4) adding 50 mL of 0.45 mol / L ascorbic acid solution to the mixed solution 3 to obtain a mixed solution 4;
[0094] (5) using an ultrasonic wave with a power of 240 W to sonicate the mixed solution 4 for 20 minutes to obtain a white precipitate;
[0095] (6) Use a separatory funnel to separate the white precipitate obtained from the reaction from the reactants;
[0096] (7) The filtered white precipitate was washed once with 40 mL of deionized water and ethanol, and dried in a 70°C air dryer for 4 hours.
[0097] (8) The powder obtained after drying is the target product.
[0098] Compared with Example 3, the preparation process of Comparative Example 3 added an excess of ascorbic acid solution (same volume, increased concentration). In order to obtain the morphology of the obtained sample, we conducted a field emission scanning electron microscope test on the sample obtained in Example 3, as shown in the attached figure. Figure 7 The sample obtained in comparative example 3 is not fishbone-shaped. This is because the excess ascorbic acid solution accelerates the reaction rate, and the faster crystal growth rate causes the original CuBr crystal nucleus in the reaction solution to be unable to grow complete fishbone-shaped nanocrystals under microwave assistance.
[0099] From the results of Comparative Examples 1, 2 and 3, it can be concluded that the key technology for the successful preparation of fishbone-shaped CuBr in the present invention is:
[0100] 1) Using ultrasound as a reaction condition;
[0101] 2) adding hydrochloric acid solution to lower the pH value of the reaction solution;
[0102] 3) Adjust the amount of reducing agent (ascorbic acid) to control the reaction rate. Only at a slower reaction rate can the mechanical energy of ultrasound successfully assist the original CuBr nuclei to grow into fishbone-shaped CuBr nanocrystals.
[0103] Application Example 1: Photocatalytic dissolution and degradation of methyl orange by the sample obtained in Example 1
[0104] In order to explore the photocatalytic performance of the obtained fishbone-shaped CuBr, the CuBr nanocrystals obtained in Example 1 were used to photocatalyze the degradation of methyl orange solution. The initial concentration of the methyl orange solution was 40 mg / L. In order to explore the photocatalytic performance, we gave the absorption spectra of different reaction times. Figure 8 As shown, after 2 hours of dark adsorption (reaching adsorption equilibrium), the absorption peak of methyl orange dye decreased significantly (concentration decreased by 54%). The above application examples prove that the fishbone-shaped CuBr has a strong adsorption capacity for methyl orange molecules.
[0105] Subsequently, under visible light irradiation, the absorption peak of the methyl orange solution continued to decrease as the reaction time progressed. This proved that the fishbone-shaped CuBr nanocrystals have the ability to photocatalyze the degradation of dyes. After 45 minutes of photocatalysis, the remaining 46% of the methyl orange solution was almost completely degraded.
[0106] Compared with other photocatalysts, fishbone-shaped CuBr has low cost, environmentally friendly preparation method, and excellent photocatalytic application performance.
[0107] In summary, this article provides a fishbone-shaped CuBr nanocrystal and a preparation method thereof, and the obtained product can be used for photocatalytic degradation of methyl orange solution. It should be noted that the above is a preferred embodiment of the invention, and for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A fishbone-shaped CuBr nanocrystal and a preparation method thereof, characterized in that: The steps of the CuBr nanocrystal preparation method include the following: (1) using CuCl2 as solute and deionized water as solvent to prepare a CuCl2 solution with a concentration of 5.0-5.5 mg / mL to obtain a mixed solution 1; (2) adding a 0.5 mol / L hydrochloric acid solution to the mixed solution 1 in proportion and mixing evenly to obtain a mixed solution 2; (3) adding KBr powder to the mixed solution 2 in proportion and mixing evenly to obtain a mixed solution 3; (4) adding an ascorbic acid solution having a concentration of 0.20-0.45 mol / L to the mixed solution 3 in proportion to obtain a mixed solution 4; (5) using 240 W ultrasonic wave to sonicate the mixed solution 4 for 10-20 minutes to obtain a white precipitate; (6) Use a separatory funnel to separate the white precipitate from the reaction solution; (7) Wash the filtered white precipitate with deionized water and ethanol 1-2 times each; (8) using a blast dryer to dry the white precipitate, and the powder after drying is the fishbone-shaped CuBr nanocrystal; Step 2) adding hydrochloric acid solution in a volume ratio of 1:15 to 2:15 to the mixed solution 1; Step 3) The amount of KBr added is 25-50 mg KBr per ml of mixed solution 2; Step 4) adding ascorbic acid solution to mixed solution 3 in a volume ratio of 5:16-5:8; Step 8) The air drier is preferably at 40-70 degrees Celsius.
2. A fishbone-shaped CuBr nanocrystal, characterized in that: The fishbone-shaped CuBr nanocrystals are obtained by the preparation method described in claim 1.
Citation Information
Patent Citations
Method for preparing small-size CuBr nano-particles
CN113044874A
CuBr nanowire and preparation method thereof
CN114427113A
Preparation method of tubular metal catalyst
CN102407106A
Method for preparing copper indium diselenide nanometer powder
CN102476791A